The role of board of directors in the establishment of risk management committee - Ishak, Suhaimi; Mohamad Nor, Mohamad Naimi (EDP Sciences, 2017)
The objective of the study is to discuss the roles of board of directors in the establishment of risk management committee for Malaysian’s public listed companies.In Malaysia, based on the Malaysian Code on Corporate Governance (MCCG), (2007; 2012) clearly stated the role and responsibility of the board of directors toward the risk management activities.At the Corporate Governance Week 2010 and 2011 as well, the chairman of the Security Commission Malaysia highlighted the responsibility of the board of directors in risk management processes and she expressed concern over the failure of the board of directors to establish appropriate measures for the risk management process in the company.The statement of the chairman of Security Commission Malaysia is in line with MCCG’s best practices (2000; 2007; 2012), i.e., the board of directors should identify principle risks and ensure the implementation of an appropriate system to manage these risks.